Hypoxia-induced PIM kinase and laminin-activated integrin α6 mediate resistance to PI3K inhibitors in bone-metastatic CRPC - Toth, Rachel K (Am J Clin Exp Urol, 2019)
Bone-metastatic castration-resistant prostate cancer (CRPC) is lethal due to inherent resistance to androgen deprivation therapy, chemotherapy, and targeted therapies. Despite the fact that a majority of CRPC patients (approximately 70%) harbor a constitutively active PI3K survival pathway, targeting the PI3K/mTOR pathway has failed to increase overall survival in clinical trials. Here, we identified two separate and independent survival pathways induced by the bone tumor microenvironment that are hyperactivated in CRPC and confer resistance to PI3K inhibitors. The first pathway involves integrin α6β1-mediated adhesion to laminin and the second involves hypoxia-induced expression of PIM kinases. In vitro and in vivo models demonstrate that these pathways transduce parallel but independent signals that promote survival by reducing oxidative stress and preventing cell death. We further demonstrate that both pathways drive resistance to PI3K inhibitors in PTEN-negative tumors. These results provide preclinical evidence that combined inhibition of integrin α6β1 and PIM kinase in CRPC is required to overcome tumor microenvironment-mediated resistance to PI3K inhibitors in PTEN-negative tumors within the hypoxic and laminin-rich bone microenvironment.